Factors Affecting Willingness to Pay for Outpatient Services at RSU Tangerang Selatan - Astrilia, Farah Elena; Hadiwiardjo, Yanti Harjono; Soeryo, Gatot (Disease Prevention and Public Health Journal, 2021)
Background: The government established a national health insurance program (NHI) to increase access to health services but the program is still not optimal, it affects the number of hospital visits and income. Therefore it required an analysis of patient’s willingness to pay out of pocket for outpatient services. The purpose of this study was to determine factors affecting patient’s willingness to pay. Method: This research is a cross sectional study involving 124 internal medicine outpatients at General Hospital (RSU) South Tangerang City in November 2019. Data were obtained from a questionnaire. Patient’s income, information, treatment experience, health insurance, distance to hospital, health service, ability to pay, and willingness to pay was investigated using chi square and logistic regression analysis. Results: The results outcomes showed that the level of willingness to pay of respondents is quite high and is influenced by patient’s income (p = 0.001), information (p = 0.045), treatment experience (p = 0.010), and ability to pay (ATP) (p = 0.001).  Factors that have the most significant associations were patient’s ability to pay (OR = 14,502). Conclusion: Patient’s income, information, treatment experience, and ATP affect the willingness to pay of patients.